2022
DOI: 10.1039/d1gc04277g
|View full text |Cite
|
Sign up to set email alerts
|

Study on the removal of lignin from pre-hydrolysis liquor by laccase-induced polymerization and the conversion of xylose to furfural

Abstract: Eucalyptus dissolving kraft pulp pre-hydrolysis Liquor (PHL) is rich in sugar and other biomass resources, which can produce furfural and may serve as a platform molecule for sustainable fuel production....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…From Figure c, it can be seen that the apparent color of the final liquid was dark brownish yellow either in pure HAP catalysis or Ce-HAP catalysis; however, the liquid after Ce-HAP catalysis showed a lighter color. This result confirms that there were more side reactions involving the production of humic substances during HAP catalysis . In addition, the three-dimensional excitation-emission matrix (3D EEM) fluorescence spectra of the obtained liquids (Figure d) indicated a main absorption at emission >380 nm/excitation >250 nm contributed by heterocyclic oxygen and aldehyde groups, possibly bearing the formation of furfurals.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…From Figure c, it can be seen that the apparent color of the final liquid was dark brownish yellow either in pure HAP catalysis or Ce-HAP catalysis; however, the liquid after Ce-HAP catalysis showed a lighter color. This result confirms that there were more side reactions involving the production of humic substances during HAP catalysis . In addition, the three-dimensional excitation-emission matrix (3D EEM) fluorescence spectra of the obtained liquids (Figure d) indicated a main absorption at emission >380 nm/excitation >250 nm contributed by heterocyclic oxygen and aldehyde groups, possibly bearing the formation of furfurals.…”
Section: Resultssupporting
confidence: 66%
“…This result confirms that there were more side reactions involving the production of humic substances during HAP catalysis. 47 In addition, the three-dimensional excitationemission matrix (3D EEM) fluorescence spectra of the obtained liquids (Figure 8d) indicated a main absorption at emission >380 nm/excitation >250 nm contributed by heterocyclic oxygen and aldehyde groups, 48 possibly bearing the formation of furfurals.…”
Section: Hydrothermal Catalytic Process Of Bsf Biomass Over Ce-hap 23...mentioning
confidence: 96%
“…Because exolaccase-induced BPA removal was completely limited in the absence of O 2 . Subsequently, these radical intermediates were stochastically coupled to produce the polymeric products [ 46 ]. Such a process involved two aspects: one was self-polymerization and the other was co-polymerization [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cleavage of β ‐O‐4 and 5‐5), (h) hydroxyl oxidation on lignin side chain C‐α to form a carbonyl group, and (i) aliphatic carbon‐carbon bond and lignin side chain cleavage. Liu et al [61] . showed that the formation of 5‐5′ and 4‐O‐5′ bonds are the main reaction of laccase oxidation, and occasionally β ‐O‐4′ bonds are formed.…”
Section: Enzyme Catalysis For Lignocellulose Degradationmentioning
confidence: 99%